VIETNAMESE ENGLISH ACCENT VS AMERICAN ENGLISH ACCENT: LOCATING THE PHONOLOGICAL VARIATION - Tri Kurnia Putri Utami; Suprayogi - Suprayogi (Linguistics and Literature Students' Journal, 2022)
Accent is something important in communication things. There are intonation, tone, stress, rhythm and segmental also supra segmental features in an accent. It has lot of function for all the speakers from all over the world when two speakers using the languages to communicate. The objective of this study is to compare Vietnamese English accent and American English accent by seeing the consonants production from each English language. The writer investigated supra segmental features, sound changes, and correspondences to disclose the comparison to the accents. Moreover, this analysis applied qualitative method in which data were obtaibed through interview and some instruments such as a spoken language in a transcription form, facebook messenger, whatsapp and audio recording. The findings show that the number of the consonants production in Vietnamese is not the same with English Consonants. Several deletion or apocopate and addition or paragog occurred.Keywords: American English accents, comparing, phonology, sound correspondence, Vietnamese English accent